Analysis on the development of legislations governing Shariah advisory council of Bank Negara Malaysia - Hussain, Mohammad Azam; Hassan, Rusni; Hasan, Aznan (Universiti Malaya, 2015)
The establishment of Shariah Advisory Council under the aegis of Bank Negara Malaysia in 1997 was the best solution taken by the Government to harmonize the issue of divergence of Shariah opinions among the Shariah committees established by the Islamic banks and takaful operators. Since then, the Shariah Advisory Council has been regulated by several statutes which provide the legal framework of such a Council. Using a historical approach, this article highlights the development of the legal framework of Shariah Advisory Council since its establishment. Comparative analysis method is used to compare the existing legislation to the previous one. Finally, the article found that the Central Bank of Malaysia Act 2009 (Act 701) provides a comprehensive legal framework to regulate Shariah Advisory Council compared to the previous statutes.